2013
DOI: 10.2147/cia.s40221
|View full text |Cite
|
Sign up to set email alerts
|

Differing approaches to falls and fracture prevention between Australia and Colombia

Abstract: Falls and fractures are major causes of morbidity and mortality in older people. More importantly, previous falls and/or fractures are the most important predictors of further events. Therefore, secondary prevention programs for falls and fractures are highly needed. However, the question is whether a secondary prevention model should focus on falls prevention alone or should be implemented in combination with fracture prevention. By comparing a falls prevention clinic in Manizales (Colombia) versus a falls an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Reductions in falls and falls-related injuries are highly associated with clinical interventions,2 4 9 which could have an ever-stronger beneficial impact would fracture prevention be integrated in the usual model of care. Therefore, it has been previously proposed that falls clinic be operationally linked to osteoporosis services such as FFC, which would facilitate a combined falls and fracture prevention in older persons 32 33. Discordant findings from other studies, where no change was observed, may also be related to their patient profile 9 10…”
Section: Discussionmentioning
confidence: 95%
“…Reductions in falls and falls-related injuries are highly associated with clinical interventions,2 4 9 which could have an ever-stronger beneficial impact would fracture prevention be integrated in the usual model of care. Therefore, it has been previously proposed that falls clinic be operationally linked to osteoporosis services such as FFC, which would facilitate a combined falls and fracture prevention in older persons 32 33. Discordant findings from other studies, where no change was observed, may also be related to their patient profile 9 10…”
Section: Discussionmentioning
confidence: 95%